DAMPAK PENGAWET PARABEN TERHADAP KESEHATAN MANUSIA: LITERATURE REVIEW - Fathimah Effendy, Nur Amalia (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2022)
Parabens are one of the most common preservatives used in products circulating in the community. Parabens are used not only alone but can be combined with other parabens. Parabens can enter the human body through the skin and parenterally. Average total daily paraben exposure is estimated at 76 mg, with cosmetics and personal care products reaching 50 mg, 25 mg from pharmaceutical products, and 1 mg from food. Based on BPOM regulation Number 18 of 2015 concerning technical requirements for preservatives, the limit for single parabens used is 0.14% and mixed parabens is 0.8%. If it exceeds these provisions, it will cause skin irritation and allergies. The method in this research is a literature study sourced from Google Scholar and Pubmed with the year of publication of the literature for the last 10 years in the range of 2012 to 2022. The results of this study discuss how the impact of parabens on human health is found that parabens have a role in obesity, increased asthma reports, affect the menstrual cycle, genotoxic effects, cytotoxic effects, and breast.